2.7k views
4 votes
Find the value of m: −3(m − 4) = −6

m = −6
m = −2
m = 2
m = 6

2 Answers

6 votes

Answer:

m=6

Explanation:

-3m+12=-6

3m=12+6

3m=18

m=6

User Smbanaei
by
5.4k points
2 votes

m = 6.

Explanation:


{ \green{ \tt{ - 3}}}({ \green{ \tt{m - 4}}}) = { \green{ \tt{ - 6}}}


{ \green{ \tt{ - 3m + 12}}} = { \green{ \tt{ - 6}}}


{ \green{ \tt{3m}}} = { \green{ \tt{12}}} \: + \: { \green{ \tt{6}}}


{ \green{ \tt{3m}}} = { \green{ \tt{18}}}


{ \green{ \tt{m}}} = \frac{ \green{ \tt{18}}}{ \green{ \tt{3}}}


{ \green{ \tt{m}}} = { \red{ \mathfrak{6}}}

User Tim Holum
by
5.3k points